2019
DOI: 10.1093/nar/gkz007
|View full text |Cite
|
Sign up to set email alerts
|

Single cell analysis reveals the involvement of the long non-coding RNA Pvt1 in the modulation of muscle atrophy and mitochondrial network

Abstract: Long non-coding RNAs (lncRNAs) are emerging as important players in the regulation of several aspects of cellular biology. For a better comprehension of their function, it is fundamental to determine their tissue or cell specificity and to identify their subcellular localization. In fact, the activity of lncRNAs may vary according to cell and tissue specificity and subcellular compartmentalization. Myofibers are the smallest complete contractile system of skeletal muscle influencing its contraction velocity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 98 publications
1
57
0
Order By: Relevance
“…We functionally discussed the involvement of the lncRNA Pvt1 in the modulation of muscle atrophy and mitochondrial network. Our findings suggested that Pvt1 can modulate the expression of c-Myc, which in turn regulates Bcl-2, having an effect on autophagy and apoptosis that are strictly linked to the conformation of the mitochondrial network [114].…”
Section: Lncrnas In Differentiated Cellsmentioning
confidence: 70%
See 4 more Smart Citations
“…We functionally discussed the involvement of the lncRNA Pvt1 in the modulation of muscle atrophy and mitochondrial network. Our findings suggested that Pvt1 can modulate the expression of c-Myc, which in turn regulates Bcl-2, having an effect on autophagy and apoptosis that are strictly linked to the conformation of the mitochondrial network [114].…”
Section: Lncrnas In Differentiated Cellsmentioning
confidence: 70%
“…We revealed that cells with different metabolic properties express different lncRNAs. Moreover, we revealed that some differentially expressed lncRNAs localize differently in cellular compartments according to cell metabolism and lncRNA isoform [114]. This last result suggests that the same lncRNA could have different roles in different cells and that the same might be true for different isoforms of the same lncRNA.…”
Section: Lncrnas In Differentiated Cellsmentioning
confidence: 71%
See 3 more Smart Citations